between ABO blood group and breast cancer at AL-Nassyria city / Iraq - Mehdi, Layla (University of Thi-Qar Journal of Science, 2008)
The current study included 200 patients with breast cancer thatresemble to patient samples were collected from AL-Nassyria hospital also279 samples as control which was collected from blood bank at ALNassiryiaprovince . The study attempted to correlate ABO blood groupwith incidence to breast cancer .The results shown that type A of ABOblood group high frequency then followed by type O with in AL-Nassyriaregion also the results reported that A, B, O and AB blood groupsfrequencies of patient samples percentage were 60%, 20%, 10% and 10%respectively as well as the ABO blood groups frequencies of control samplespercentage were 26%, 28%,38% and 8% respectively. The results observedthere is high significant differences between ABO blood group frequenciesof cancer patients and ABO blood group frequencies of control samples.The results indicated that the blood type should be considered one of riskfactor as well as regarded as preclinical marker.